Reductive Heck Reactions and [3+2] Cycloadditions of Unsaturated N,N'-Bistricyclic Imides - Gul, Melek; Kulu, Irem; Gunkara, Omer Tahir; Ocal, Nuket (SLOVENSKO KEMIJSKO DRUSTVO, 2013)
The C-C coupling of N,N'-bis(5-norbornene-2,3-dicarboximide) (3) and N,N'-bis(7-oxa-5-norbornene-2,3-dicarboximide) (6) with aryl and heteroaryl iodides gave under reductive Heck conditions the C-aryl(hetaryl), substituted N,N'bistricyclic imides 7a-f and 8a,b. The fused spiro-1,3-indandionolylpyrrolidine compounds, 9, 10 and 11 were also obtained from ninhydrine, sarcosine and 3 or 6 via [3+2] cycloaddition.
Keywords: Alkenes; cycloadditions; heterocycles; hydroarylations; triyclic imides; SUBSTITUTED CYCLIC IMIDES; HYDROARYLATION; EPIBOXIDINE; ANALOGS; DICARBOXIMIDES; ANTICANCER; Chemistry